105 Cost Analysis for the Risk-Stratification of Febrile Infants ≤ 60 Days Old. (29th October 2021) - Dionisopoulos, Zachary; Strumpf, Erin; Anderson, Gregory; Guigui, Andre; Burstein, Brett
Abstract: Primary Subject area: Emergency Medicine - Paediatric Background: Fever in the first months of life is among the most common clinical problems in pediatric healthcare. Nearly 2% of all infants will be evaluated for fever in an Emergency Department (ED) and approximately 10% harbor life-threatening serious bacterial infections (SBIs). The Rochester criteria are most widely used criteria for risk-stratification and predate modern biomarkers including procalcitonin (PCT). Recently, a high-performing prediction rule incorporating PCT was derived by the Pediatric Emergency Care Applied Research Network (PECARN). At present, PCT is not available in all clinical settings, limited largely by test cost. Objectives: Compare the medical costs associated with PECARN and Rochester risk-stratification strategies using contemporary price, epidemiologic and test characteristic data. Design/Methods: We assessed hospital-level costs associated with the door-to-discharge care of all well-appearing febrile infants aged ≤ 60 days evaluated at an urban tertiary pediatric hospital between April 2016 and March 2019. Direct and indirect ED and inpatient costs were obtained from provincial Ministry of Health data. Real-world costs were then incorporated into a probabilistic model for a cohort of equal size using either Rochester or PECARN risk-stratification, accounting for the added incremental cost of PCT (24.86CAD). Models used an 8.4% pooled SBI risk, and Sn/Sp for Rochester and PECARN of 94%/49% and 98%/63%, respectively. Modeling was calculated under 4 scenarios; true positive with hospitalization, false negative with return visit and hospitalization, false positive with hospitalization, true negative with ED discharge. All costs were calculated in Canadian dollars. Results: During the 3-year study period, 1168 index infant encounters met inclusion and were analyzed for hospital trajectory costs. Median costs per infant were 323 (IQR 286-393) for infants discharged from the ED with no SBI, 2356 (IQR 1858-3120) for infants hospitalized with no SBI, 3150 (IQR 2352-4201) for hospitalized infants treated for a SBI, and 3763 (IQR 2146-5180) for infants discharged from the ED ultimately requiring hospitalization with a missed SBI. For a cohort of 1168 infants, cost-per-infant using PECARN risk-stratification was 1332 (IQR 1062-1739), compared to 1515 (IQR 1198-1992) using Rochester. PECARN criteria would be expected to produce an overall savings of 12.1% for the modeled cohort (1, 556, 432 vs 1, 769, 339). Under pessimistic and optimistic model assumptions, total savings were 4.9% and 18.3%, respectively. Costs borne by families were not considered, nor were the indirect benefits of reduced unnecessary invasive testing, hospitalizations and broad-spectrum antibiotic use. Conclusion: Risk-stratification of febrile infants using PECARN prediction rules would produce important cost-savings due to superior test characteristics offsetting upfront PCT-associated costs. Such a strategy would also likely result in unmodeled non-monetary family-centered and healthcare system benefits. Real-world cost-effectiveness studies are needed.